Second-chance summer - McNally, Jo (Romance author) (Harlequin special edition, 2022)
His biggest rival is becoming his greatest temptation. Julie Brown wants golf lessons? For golf pro Quinn Walker, Gallant Lake Resort's cheery yet determined manager is a thorn in his side. But the widowed single dad begrudgingly agrees to teach his sassy coworker the game he loves. As their lessons progress, Julie disarms Quinn in ways he can't explain...or ignore. A second chance at love is as rare as a hole in one. Can these rivals at work tee it up for love? "--